(untitled) (Bombay Hospital Journal, 2026)
Abstract: Aim: Tropical Pyomyositis presented as false positive brucellosis with right sacroiliitis joint pain Background: ). Pyomyositis, also known as “tropical pyomyositis” Myositis purulent atropica. In 90% cases the causative agent is Staphylococcus aureus Case Description: A young male presented with multiple skeletal muscle abscess with left sacroiliitis joint pain. Patient also showed false positive brucellosis antibody test with negative slide agglutination test. Conclusion: CT scan guided aspiration of pus inside the pelvic region as well as Laparoscopic drainage of pus with debridement showed Staphylococcus Aureus. Patient responded with debridement along with prolong antibiotic course. Clinical Significance: Pyomyositis is a poorly understood condition . The initial signs and symptoms are nonspecific and misleading and making it often underdiagnosed